Carbonyl-to-Alkyne Electron Donation Effects in up to 10-nm-Long, Unimolecular Oligo(p-phenylene ethynylenes) - Rajappan, Sinu C.; Vestrheim, Olav; Sharafi, Mona; Li, Jianing; Schneebeli, Severin T. (Organic Materials, 2021)
We synthesized some of the longest unimolecular oligo(p-phenylene ethynylenes) (OPEs), which are fully substituted with electron-withdrawing ester groups. An iterative convergent/divergent (a.k.a. iterative exponential growth – IEG) strategy based on Sonogashira couplings was utilized to access these sequence-defined macromolecules with up to 16 repeating units and 32 ester substituents. The carbonyl groups of the ester substituents interact with the triple bonds of the OPEs, leading to (i) unusual, angled triple bonds with increased rotational barrier, (ii) enhanced conformational disorder, and (iii) associated broadening of the UV/Vis absorption spectrum. Our results demonstrate that fully air-stable, unimolecular OPEs with ester groups can readily be accessed with IEG chemistry, providing new macromolecular backbones with unique geometrical, conformational, and photophysical properties.
Keywords: sequence-defined macromolecules; shape-defined macromolecules; Sonogashira coupling; iterative exponential growth; density functional theory; π-conjugation